Electron excitation in thin metal films due to the magnetic field of ultrashort laser pulses - Lugovskoy, Andrey; Bray, Igor (Optical Society of America, 2014)
The behavior of the conduction-band electrons in a metal film subjected to the action of an ultrashort laser pulse at normal incidence is analyzed quantum-mechanically. The pulse duration is assumed to be shorter than the electron mean free time. It is shown for the first time that electrons in the film can be excited resonantly to the higher-energy quantum well levels due to the action of the magnetic field of the wave. The numerical analysis is conducted for an electron which is initially in the lowest quantum well and has a quasi-momentum directed along the electric field. It is shown that the excitation probability due to the magnetic-field excitation mechanism can be even larger than the excitation probability due to the inverse bremsstrahlung in electron–phonon collisions.